Issues on Vector Related Diseases Transmission: People's Perception & Practices (Anwer Khan Modern Medical College Journal, 2019)
Background: The vector borne diseases pose an immense public health concern and also a growing urban and rural problem. The aim of this study was to findout the perception and practices among the rural households regarding vector related diseases in some selected villages of Dhamrai Upazila.Material and Methods: This descriptive cross sectional study was carried out among 1380 respondents by purposive sampling technique during the period from 6th to 8th January, 2018 in different villages of Dhamrai Upazila, Dhaka..Results: Then study revealed that majority of the respondents 89% were Muslims by religion and about 65% respondents were found within the age 25-55 years. (mean age 37.81±14.72 years). Out of 1380 respondents, majority 87% & 86% mentioned Mosquitos and Houseflies as vectors transmitting the diseases followed by 48% Itch mite, 45% Louse and 27% Sandflies. About 85% & 88% mentioned Malaria & Dengue fever transmitted by vectors followed by 58% Chikungunya, 42% Kala azar, 13% Filariasis and 44% Typhoid fever. However, 71%, 83%, 59% & 3% respondents mentioned Mosquito bite as the mode of transmission of Malaria, Chikungunya and Filariasis respectively. About 88%, 75%, 44% and 39% respondents mentioned Personal protection, Avoidance of water collection, Fogging and Insecticidal spraying as the vector control measures. Nevertheless, 92%, 81% and 30% respondents are found practiced Mosquito net, Mosquito coil and Screening of windows as their usual vector control measures.Conclusion: In this study community awareness in terms of perceptions, knowledge and practices regarding vector borne diseases are found deficient. There should be intensified efforts in promoting personal protective measures through creating public awareness towards prevention of vector borne diseases in the locality.Anwer Khan Modern Medical College Journal Vol. 10, No. 1: Jan 2019, P 32-37